2008
DOI: 10.1002/art.23628
|View full text |Cite
|
Sign up to set email alerts
|

An early sympathetic nervous system influence exacerbates collagen‐induced arthritis via CD4+CD25+ cells

Abstract: Objective. Activation of the sympathetic nervous system (SNS) ameliorates collagen-induced arthritis (CIA) in the late phase of the disease but aggravates it in the presymptomatic phase. The aim of the present study was to determine whether CD4؉CD25؉ T cells are influenced by the SNS of mice and play a diseasemodifying role in the early symptomatic phase of the disease.Methods. We tested the effects of the SNS on arthritis by transferring CD4؉CD25؉ T cells from sympathectomized mice immunized with type II coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 58 publications
(54 reference statements)
5
44
0
3
Order By: Relevance
“…In particular, IL-17 has a major proinflammatory role in primary and flare-up reactions of AIA, whereas IFNγ has a pronounced pro- and anti-inflammatory role in both AIA and CIA 9 23–26. Furthermore, sympathectomy modulated the number and activity of regulatory T cells in CIA and autoimmune encephalomyelitis 27 28…”
Section: Discussionmentioning
confidence: 99%
“…In particular, IL-17 has a major proinflammatory role in primary and flare-up reactions of AIA, whereas IFNγ has a pronounced pro- and anti-inflammatory role in both AIA and CIA 9 23–26. Furthermore, sympathectomy modulated the number and activity of regulatory T cells in CIA and autoimmune encephalomyelitis 27 28…”
Section: Discussionmentioning
confidence: 99%
“…The transition phase from pro-to antiinflammatory effects by the SNS is thought to lie between day 30 and day 55 after immunization in murine CIA (14,35). It has been suggested that the early, proinflammatory effects are caused by SNS-induced redistribution, migration and chemotaxis of leukocytes toward the site of inflammation (30,35 T cells from the sympathectomized CIA mice also displayed a reduced cytokine response (36). β2-Adrenergic receptor agonists or antagonists in experimental arthritis.…”
Section: Immunomodulatory Effect Of Agents Targeting the Sympathetic mentioning
confidence: 99%
“…The influence of adrenergic signaling and the loss of sympathetic nerve fibers in the inflamed tissue in RA has been demonstrated in several animal models of arthritis (68). Sympathectomy in the early phase of the disease has been shown to ameliorate experimental arthritis, indicating the pro-inflammatory influence of adrenergic signaling (69). During arthritic inflammation, nerve repulsion factors released by macrophages result in the withdrawal of sympathetic neurons from the synovial tissue and the subsequent depletion of synovial norepinephrine concentrations (68).…”
Section: Neural-immune Circuits In Inflammationmentioning
confidence: 99%